Pemberdayaan Kayo Homestay Bromo Melalui Implementasi Integrated Marketing Communication Sebagai Upaya Meningkatkan Kunjungan Wisatawan - Junaidi; Raihan Wishal Nafis; M.Novan Fithrianto; Judi Suharsono; Mufid Andrianata; Lukman Hakim (Fakultas Teknik, Universitas PGRI Banyuwangi, 2025)
This community service program was designed to empower Kayo Homestay, located in Tosari Village, Pasuruan, through the implementation of Integrated Marketing Communication (IMC) as an effort to increase tourist visits. The program addressed several managerial and marketing challenges, including the lack of standardized operational procedures, inadequate financial management systems, limited digital marketing utilization, and weak brand identity. The intervention was carried out in five stages: socialization, training, technology implementation, mentoring and evaluation, and program sustainability. The results indicate significant improvements in both operational efficiency and market visibility. The implementation of a website-based property management system increased room bookings by approximately 50% compared to the period prior to the intervention. Additionally, the use of digital financial applications improved financial transparency and reduced manual errors by 30%. From a marketing perspective, the development of digital content and social media strategies strengthened brand positioning and enhanced customer engagement. These findings are consistent with previous studies emphasizing the role of digital marketing and branding in improving the competitiveness of community-based tourism businesses. Overall, this program demonstrates that the integration of IMC, digital tools, and community empowerment strategies can enhance the competitiveness and sustainability of homestay businesses while contributing to local economic growth.